A clinical case of extremely severe COVID-19 with a favourable outcome - A. I. Bolgova; L. A. Aschina; N. I. Baranova; O. N. Lesina (Журнал инфектологии)
COVID-19 is an infectious disease that can progress from carrier and mild symptoms of acute respiratory infections to bilateral pneumonia, severe respiratory failure, acute respiratory distress syndrome (ARDS), multiorgan failure, sepsis and shock. One of the predictors of severe course of infection is advanced age and comorbidities. In this work we considered a clinical case of COVID-19 patient S., 86 years old, who was admitted to the hospital, to the intensive care unit on the 10th day of the disease, in an extremely severe condition. A diagnosis of bilateral polisegmental pneumonia with 70% lung involvement caused by SARS-CoV-2 virus was made. In addition to antiviral therapy with remdesivir and symptomatic therapy, pathogenetic therapy with tocilizumab was applied. On admission, the patient had leukopenia, thrombocytopenia, elevated values of COE, urea, significant elevation of inflammatory markers CRP and D-dimer, as well as pCo2. During inpatient treatment, positive dynamics of the condition and laboratory parameters were observed. The patient was discharged in satisfactory condition, all laboratory parameters were normalised, except for a slight increase in CRP and pCO2 levels. Despite the age of the patient and the severity of COVID-19 course, the combined use of drugs with multidirectional action, including tocilizumab, may improve the outcome of the disease.